Adsorptive removal of trivalent and pentavalent arsenic from aqueous solutions using iron and copper impregnated melanin extracted from the marine bacterium Pseudomonas stutzeri. (February 2020) - Manirethan, Vishnu; Raval, Keyur; Balakrishnan, Raj Mohan
Abstract: The metalloid arsenic is one of the most conspicuous groundwater contaminants in the Indian subcontinent and its removal from aqueous medium is the main focus of this study. The study aims at functionalising melanin using iron and copper for the efficient removal of arsenic and rendering water fit for consumption. Melanin obtained from the marine bacteria Pseudomonas stutzeri was functionalised by iron impregnation (Fe-melanin) and copper impregnation (Cu-melanin). Morphological studies using FESEM portrayed the impregnated iron and copper granules on the surface of melanin, while XRD analysis confirmed the presence of Fe2 O3 and CuO on melanin. Adsorption studies on As (V) and As (III) were conducted using Fe-melanin and Cu-melanin for different operating variables like pH, temperature and contact time. More than 99% per cent of As (III) and As (V) from water was removed at a pH range between 4 and 6 within 50 min in the case of Fe-melanin and 80 min for Cu-melanin. Adsorption equilibrium studies showed better fit with Langmuir adsorption isotherm and had good agreement with Redlich-Peterson's three-parameter model. The maximum adsorption capacities of Fe-melanin and Cu-melanin obtained from Langmuir adsorption model are 50.12 and 20.39 mg/g, respectively, for As (V) and similarly 39.98 and 19.52 mg/g, respectively, for As (III). Arsenic-binding to the functionalised melanin was confirmed using FT-IR and the XPS analysis. Reuse of the adsorbent was effectively done by desorbing the iron and copper together with the bound As (III) and As (V) and further re-impregnation of iron and copper in melanin. Re-functionalised melanin showed 99% adsorption efficiency up to four cycles of adsorption/desorption. Graphical abstract: Image 1 Highlights: Melanin was produced from the marine bacteria Pseudomonas stutzeri HMGM-7. Iron and copper are impregnated on biosynthesized melanin to remove As (III) and As (V) from groundwater. Efficient in the removal of As (III) and As (V) from water at concentrations below 10 mg/L and with low adsorbent dosage. Regeneration and reuse with more than 99% efficiency of arsenic adsorption in successive adsorption-desorption cycles. Abstract : A novel iron and copper impregnated melanin was synthesized to remove As (III) and As (V) from groundwater and the adsorption process was optimized.